Modularity and Temporal Reasoning: a Logic Programming Approach - Nogueira, Vitor (2009)
Albeit temporal reasoning and modularity are very prolific fields of research in Logic Programming (LP), we find few examples of their integration. In this paper we propose the addition of temporal annotations to a modular extension of LP. Moreover, besides an illustrative example we also provide a sketch for a compiler, allowing this way for the development of applications based such language.